Cost analysis of a patient blood management program for patients undergoing gastric cancer surgery. Issue 1 (January 2023) - Jericó, Carlos; Puértolas, Noelia; Osorio, Javier; Miranda, Coro; Santamaría, Maite; Artigau, Eva; Galofré, Gonzalo; Garsot, Elisenda; Luna, Alexis; Aldeano, Aurora; Olona, Carles; Pulido, Laura; et al.
Abstract: Patient Blood Management (PBM) programs have probed to reduce blood transfusions and postoperative complications following gastric cancer resection, but evidence on their economic benefit is scarce. A recent prospective interventional study of our group described a reduction in transfusions, infectious complications and length of stay after implementation of a multicenter PBM program in patients undergoing elective gastric cancer resection with curative intent. The aim of the present study was to analyze the economic impact associated with these clinical benefits. The mean [and 95% CI] of total healthcare cost per patient was lower (−1955 [-3764,  −119] €) after the PBM program implementation. The main drivers of this reduction were the hospital stay (−1847 [-3161,  −553] €), blood transfusions (−100 [-145,  −56] €), and post-operative complications (−162 [-718, 411] €). Total societal cost was reduced by −2243 [-4244,  −210] € per patient. These findings highlight the potential economic benefit of PBM strategies. Highlights: This multicentre study on 789 patients submitted to gastric cancer surgery found that implementation of a Patient Blood Management program was associated to a expense reduction of −1955 € per patient [95% CI -3764,  −119] in healthcare, and of −2243 € [95% CI -4244,  −210] in societal costs. The main drivers of this economic saving were reductions in hospital stay, blood transfusions, and post-operative complications.